Babies born to obese mothers: How are the characteristics and outcomes? - Julia Kasab; Ari Yunanto; Pudji Andayani; Pricilia Gunawan Halim (International Journal of Public Health Science (IJPHS), 2022)
Obesity during pregnancy puts the mothers at risk of significant medical conditions and is also associated with some medical problems in neonates. This study aims to analyze the characteristics and outcomes of babies born to obese mothers at a tertiary hospital in Banjarmasin, Ulin General Hospital. This study was observational using secondary data of neonates born at Ulin General Hospital Banjarmasin, January 2020 - October 2021. The total number of subjects included in this study was 110, divided into two groups based on the obesity status of the mother (obese and non-obese). Common maternal characteristics of the obese mothers were having higher education (43.6%), being a housewife (67.3%), being diagnosed with severe preeclampsia (58.2%), and having infection risk (54.5%). Of the babies, 100% were delivered by C-section, 21.8% were premature, 12.7% had excessive birth weight, and 54.5% were requiring treatment before being discharged. For the outcomes, the average length of stay was 4.5±3.6 days (p<0.05) and the need for NICU admission was 20% (p>0.05). The most compelling characteristics and outcomes of babies born to obese mothers in this study were delivered by C-section, had excessive birth weight, unwell babies, and had a longer hospital stay.